Educator Excellence in the Era of Society 5.0: A Hadith Perspective - Onilivia, Viva Fadma; Noptario, Noptario (HEUTAGOGIA: Journal of Islamic Education, 2024)
In the disruptive era of Society 5.0, educators are required to continuously learn and adapt to technological advancements. This study aims to examine the concept of an exemplary educator from the perspective of Hadith, providing a reference for teachers to develop their potential in accordance with religious teachings. Utilizing a qualitative research approach and library research methods, this study explores various sources such as books, articles, and other relevant literature. The findings emphasize that to be a quality educator in the sophisticated era of Society 5.0, one must be adept at embracing change, utilizing technology effectively, and guiding students towards both worldly success and spiritual fulfillment. The discussion underscores the importance of balancing technological proficiency with religious principles, portraying educators as critical thinkers who embody the teachings of Prophet Muhammad SAW. This study contributes to the Islamic educational knowledge base by highlighting that the efforts to create excellent educators are also advocated in Islam through Hadith, thereby ensuring that future generations receive the best education aligned with religious teachings.